PERANCANGAN SISTEM DELIVERY ONLINE BERBASIS WEB MENGGUNAKAN METODE NAÏVE BAYES CLASSIFIER DI RUMAH MAKAN WAROENG KAMPOENG JEPUN KOTA CIREBON - Muhammad Habri Ridwan (INFOKOM, 2018)
The development of increasingly advanced and restaurant business is increasing every restaurant tries to present something new and unique to its customers. Many restaurants are managed successfully, but many of them fail in the restaurant business, the need for evaluation to the real thing is a lot of restaurants that fail to cause other than flavors. There is another more important factor is the service provided to customers. Need for improvement and development of the service in the restaurant so that customers are satisfied with the services provided.Implementation of an online booking system web-based delivery. One of the services that take advantage of the changing times of the all this technology. With features - menu features eat, that is complete in the Web. Can be ordered directly online.Created using PHP programming language, Bootstrap framework as a design interface, MySQL as database.dan method of data mining as data analysis.With this application could be a solution tools to provide convenience to customers in the food menu book Delivery At Home Spot Waroeng Kampoeng Jepun Cirebon city.